Nonscarring alopecia in systemic lupus erythematosus: A cross-sectional study with trichoscopic, histopathologic, and immunopathologic analyses - Kumutnart Chanprapaph (2020)
© 2019 American Academy of Dermatology, Inc. Background: Nonscarring alopecia in systemic lupus erythematosus (SLE) is widely recognized, but reports on its clinical, trichoscopic, histopathologic, and direct immunofluorescence (DIF) features are still limited. Objective: To summarize the different clinical patterns, trichoscopic, histopathologic, and DIF features of nonscarring alopecia in SLE and to prove its association with disease activity. Methods: Patients with SLE with and without nonscarring alopecia had full physical/trichoscopic examination and scalp biopsy. Their disease activity scores and laboratory data were evaluated and statistically analyzed. Results: Thirty-two patients with SLE had different patterns of nonscarring alopecia, including mild diffuse alopecia (43.8% [n = 14]), severe diffuse alopecia (15.6% [n = 5]), patchy alopecia (28.1% [n = 9]), and lupus hair (12.5% [n = 4]). The most common trichoscopic findings were arborizing/interconnecting vessels (83% [n = 26]). Histopathologic examination showed interface changes along the dermoepidermal junction (87.5% [n = 28]) and follicular epithelium (40.6% [n = 13]). On DIF, homogeneous granular deposition was detected along the dermoepidermal junction (78.1% [n = 25]) and follicular epithelium (78.1% [n = 25]). When compared with 10 patients with SLE without alopecia, there was a significantly higher SLE Disease Activity Index 2000 score and prevalence of proteinuria (>1 g/d). Limitations: This was a small, cross-sectional, single-center study. Conclusions: Nonscarring alopecia in SLE shows lupus erythematosus–specific changes on histology and DIF. Hair loss in SLE can be considered as an indicator of active disease.